Biosynthetic graft failure to replace infected infrainguinal bypass as developing infection due to Morganella morganii leading to disrupture of the anastomosis. Case report. (2017) - Zenunaj, Gladiol; Spataro, Claudio; Traina, Luca; Gasbarro, Vincenzo
Highlights: Infection of infrainguinal bypass is a challenging complication with a high risk rate mortality and limb loss. Biosynthetic grafts are considered as the last chance to deal with bypass infection and if they fail other solutions are required. Besides occlusion of biosynthetic grafts other complications may occur during the follow up such as infection and haemorrhage. Recurrent infection of two different grafts used for infrainguinal bypass makes meaningless the use of other materials at the same surgical site. Extra- anatomical bypass avoiding the compromised and complicated surgical site could be a solution to assure limb salvage and patient survival. Abstract: Introduction: Biosynthetic prosthesis has become the trend to carry out arterial reconstruction in infected sites since considered to be resistant to infection. Late graft occlusion is the only complication reported in literature so far. We report a case of biosynthetic graft infection which led to early detachment of the femoral anastomosis of a femoral-popliteal above-knee bypass. Material: A 76-year-old man developed groin infection 3 months later after performing an ePTFE femoral-popliteal above-knee bypass for critical limb ischemia. He was re-admitted for groin infection involving the vascular structures. Explantation of the existing bypass and its replacement with a biosynthetic graft (omniflow II) was performed. Detachment of the proximal anastomosis occurred 6 days later leading to groin haematoma. Consequently, retroperitoneal access was performed for clamping the external iliac artery so as to control haemorrhage followed by explantation of the biosynthetic graft. An external iliac-popliteal above-knee bypass was tailored in order to save the limb and it was performed using a transobturator approach avoiding the infected site. In both cases bacterial cultures resulted positive for Morganella Morganii. The groin wound was treated separately with negative pressure medication healing definitively within 20 days and after 3-month follow-up the bypass was still patent. Conclusion: This is the first report of biosynthetic graft infection used for infrainguinal reconstruction leading to haemorrhage due to anastomosis disrupture. Using an extra-anatomical access for providing blood inflow to the leg avoiding the infected site and treating safely the groin wound with VAC therapy revealed to be a valid approach.